Conflicto Armado, Desplazamiento Forzado y Resiliencia: Relatos de Vida en Adolescentes (2016)
Armed Conflict is one of the events that has left more victims throughout the history of our country, this study specifically takes forced displacement. This situation was addressed based on the experiences of three young people between 16 and 18 years, so that through his account, it is able to identify the Protectors External Factors Resilient present in your experience, evaluating the decision and inquiring about the family environment and social context in which they are immersed. Life stories in all three cases was used as an instrument, teenagers are students of the town of Bosa Porvenir that are part of Citadel College Educational Bosa of the day in the morning, between the eighth and tenth baccalaureate degrees. The truth is that these teenagers are in each of the areas external protective factors, being these that facilitate the development of resilience, family and social amito, along with significant others that encourage recovery and overcoming adversity, carried out by taking assertive for the present and future decisions of their lives.